Legal Certainty of Ships as an Object of Credit Guarantee in Maritime Investment - Halim, Anriz Nazaruddin (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Provisions in statutory regulations have been expressly regulated that ships weighing 7 gross tonnage (GT) or the equivalent of 20 m can obtain credit facilities by providing mortgage collateral for the ship, with the main condition being that it has been registered in the Indonesian Ship Register. . And for ships weighing less than that, it is not implied in the statutory provisions that they can be charged with a Fiduciary or Pawn. However, banks prefer to guarantee large ships with mortgages. Meanwhile, for fishing boats weighing less than 7 GT, not all banks accept them, because the value of the object being pledged as collateral is small so they cannot provide certainty whether they will be able to cover the value of the debt if a default occurs in the future. Meanwhile, if the bank accepts most of the banks, they will ask for additional collateral of different value. Apart from that, banks also require proof of financing history in other banks within a specified time period, as well as the production of other documents that small fishermen cannot afford. In the registration process, people are confused by the fact that the ship (the entire ship) is not listed in the input in the Fiduciary system, only the machines on the ship are listed.